Data center storage cost-effective strategies, implementation, and management - Smith, Hubbert. (Auerbach Publications, 2011)
"This work provides a storage industry insiders insight on how to properly scope, plan, evaluate, and implement storage technologies to maximize performance, capacity, reliability, and power savings. It covers all types of storage technology, including SAN, capacity-optimized drives, and solid-state drives. Written for IT managers, data center managers, and CIOs, the book offers strategies for minimizing risk and cost when implementing storage technology, including how to reduce air conditioning costs and overall power consumption. It also analyzes cloud technology and its effects on an organizations storage strategies"--